Enhancement in heat generation through ternary hybrid nanofluid in a periodic channel - Anum Tanveer; Iram; M.Z. Alqarni; S. Saleem; A. Al-Zubaidi (Case Studies in Thermal Engineering)
This study presents a novel analysis of peristaltic flow involving a couple stress fluid embedded with a ternary hybrid nanofluid consisting of titanium dioxide (TiO2), alumina (Al2O3), and copper (Cu) nanoparticles, with blood as the base fluid, in the presence of a magnetohydrodynamics. The investigation focuses on the combined influence of entropy generation, homogeneous-heterogeneous chemical reactions, thermal radiation, viscous dissipation, thermophoresis, Brownian motion and Joule heating. The governing equations of the system are transformed into dimensionless form and solved numerically using the NDSolve in Mathematica, based a fourth-order Runge-Kutta method for accurate and efficient results. Key findings reveal that entropy generation is significantly reduced—by up to 12 % with an increase in the Hartmann number (M) and dimensionless temperature difference (Ω). Additionally, the inclusion of thermophoresis (Nt) and Brownian motion (Nb) enhances heat transfer, leading to a 15 % increase in temperature profile compared to traditional nanofluid models. The concentration profile demonstrates a unique dependency, showing a 10 % improvement with higher heterogeneous reaction rates (H) and Schmidt number (Sc), while the velocity profile decreases by 15 % with elevated M, indicating precise control of flow behavior in MHD environments. Furthermore, the size of the trapped bolus decreases with increasing M, offering potential for enhanced biomedical applications, such as targeted drug delivery and controlled blood flow. This study is the first to explore the combined effects of ternary hybrid nanoparticles, couple stress fluids and MHD field on peristaltic motion with entropy generation. The findings provide new insights into optimizing thermal and fluid transport processes for advanced biomedical devices and industrial heat transfer systems. Specifically, the research supports the development of advanced peristaltic pump systems for drug delivery, waste removal and fluid transport in biophysiological environments.